Green InGaN Quantum Dots Breaking through Efficiency and Bandwidth Bottlenecks of Micro‐LEDs. Issue 5 (18th March 2021) - Wang, Lei; Wang, Lai; Chen, Chien‐Ju; Chen, Kai‐Chia; Hao, Zhibiao; Luo, Yi; Sun, Changzheng; Wu, Meng‐Chyi; Yu, Jiadong; Han, Yanjun; Xiong, Bing; Wang, Jian; et al.
Abstract: Micro‐LEDs are regarded as ideal light sources for next‐generation display and high‐speed visible‐light communication (VLC). However, the conventional micro‐LEDs based on InGaN quantum well (QW) active region suffer from a low efficiency under small injection (below 1 A cm −2 ) due to the size‐dependent effect and a limited 3 dB bandwidth (hundreds of MHz) due to quantum‐confined Stark effect. Here, InGaN quantum dots (QDs) are proposed as the active region of micro‐LEDs to address these challenges for their strong localization and low‐strain features. Green InGaN QDs are self‐assembled under Stranski–Krastanov (SK) and Volmer–Weber (VW) modes by using metal organic vapor phase epitaxy. The SK QDs can shift the peak efficiency of a micro‐LED to an extremely low current density of 0.5 A cm −2 (almost two orders of magnitude lower compared to QW ones) with an external quantum efficiency of 18.2% (nearly two times higher than present green micro‐LEDs). Besides, green micro‐LEDs based on VW QDs reach a 3 dB bandwidth of 1.3 GHz. These results indicate that InGaN QDs can provide an ultimate solution to micro‐LEDs for display and VLC applications, especially since they are fully compatible with current light‐emitting diode (LED) industrial technology. Abstract : Self‐assembled InGaN quantum dots (QDs) are applied to green micro‐LEDs. Stranski–Krastanov QDs facilitate the peak efficiency of a 14 µm micro‐LED shifting to 0.5 A cm −2 with an external quantum efficiency of 18.2%. Volmer–Weber QDs exhibit a short carrier lifetime of 0.56 ns, and a micro‐LED with a 3 dB modulation bandwidth of 1.3 GHz is demonstrated.